Complicated Replanted Finger, 34 Years after Revascularization. Issue 11 (November 2020) - Vanmierlo, Bert; Vanmierlo, Tim; Goubau, Jean
Abstract : Summary: Merely a few reports of late failure (later than the 7th postoperative day) of a digital replantation can be found in the literature. Discussions of the factors that might cause a late failure are concise. To our knowledge, there are no reports of failure in literature as late as the case we are presenting. An 87-year-old white man was diagnosed with acute complications of a digital replantation, 34 years after initial surgery. Ultrasound examination and an arteriography demonstrated occlusion of the arterial anastomosis. The patient's surgical file revealed scars of former replantation surgery of both the index and the middle finger. In the latter, 1 artery and 2 veins were anastomosed. Considering the age and comorbidities of the patient, revascularization of the finger was not performed. Local wound care and analgesic drugs were prescribed. After initial deterioration and ulceration, gradual improvement was noticed. Total wound healing occurred at 3 months after the initial consultation. Compared with free flap surgery in general, finger replantations are at a higher risk of late complications because digital neovascularization is directly correlated to the contact surface area. This contact surface is usually larger in other free flaps. Furthermore, diseases that deteriorate circulation most likely affect the short- and the long-term survival of a digital replantation. From this point of view, performing both volar digital arterial anastomoses, whenever possible, might reduce early as well as late failure in replantation surgery.